2020
DOI: 10.1039/d0ob00109k
|View full text |Cite
|
Sign up to set email alerts
|

Rust-derived Fe2O3 nanoparticles as a green catalyst for the one-pot synthesis of hydrazinyl thiazole derivatives

Abstract: A novel route of one-pot multicomponent reaction of tosylates, aryl aldehydes and thiosemicarbazide for the synthesis of hydrazinyl thiazole is reported using Fe2O3 NPs derived from rust iron as a catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Here we have shown different reaction strategies developed by different research groups for the synthesis of hydrazinyl thiazoles. Some of them are catalyst-free, [38,39] some are both catalyst and solvent-free, [40,41] while some are catalyzed by homogeneous, [17,[42][43][44][45][46][47][48][49][50] and heterogeneous [51][52][53][54] catalysts. All the processes have some advantages over each other and also have some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we have shown different reaction strategies developed by different research groups for the synthesis of hydrazinyl thiazoles. Some of them are catalyst-free, [38,39] some are both catalyst and solvent-free, [40,41] while some are catalyzed by homogeneous, [17,[42][43][44][45][46][47][48][49][50] and heterogeneous [51][52][53][54] catalysts. All the processes have some advantages over each other and also have some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The reported mechanism of the nano-SiO 2 catalyzed reaction is shown in figure 4. In 2020 Gurav et al reported [54] an efficient and green onepot procedure for the synthesis of hydrazinyl thiazoles catalyzed by rust-derived Fe 2 O 3 nanoparticles (Nano-Fe 2 O 3 ) in water. They synthesized the desired product 71 by reacting aryl aldehydes 69, thiosemicarbazide 10, and aromatic tosylates 70 in the water at room temperature and in presence of Nano-Fe 2 O 3 catalyst (Scheme 20).…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%
“…The first method employs a two-step condensationcyclization sequence between a carbonyl function and thiosemicarbazide to yield thiosemicarbazone, which is then cyclized with α-halo carbonyl compound to produce hydrazinyl thiazole derivatives. In current literature, Reddys, [9] Mokhtary, [10] Hangirgekar, [11] Kannan, [12] Chobe, [13] Chinnaraja, [14] Bhosale, [15] and Iqbal [16] have demonstrated the rapid synthesis of the hydrazinyl thiazole motif utilizing various catalytic models.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we are able to devise a facile, safe, and economically feasible synthesis route to obtain the bulk amount of (Gurav et al 2020a). These methodologies mostly prepared composite type catalyst with hard and di cult preparation conditions which ultimately increase the process cost.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion of ferrous metals in soil is a signi cant problem in oil and water storage tanks, transported pipelines, and cooling water pipeline distribution systems (Karthick et al 2020). Current technologies are neither e cient to impede the corrosion ultimately nor effective in the recycling of waste iron rust (Babar et al 2018 (Gurav et al 2020a). These methodologies mostly prepared composite type catalyst with hard and di cult preparation conditions which ultimately increase the process cost.…”
Section: Introductionmentioning
confidence: 99%